STUDY OF ANTHROPOMETRY OF PRODUCTION SPACE FOR HOUSEHOLD INDUSTRY FURNITURE IN MAHMUD VILLAGE, BANDUNG DISTRICT - Regina Cecilia; Anggoro Cipto Ismoyo (Ide dan Dialog Desain Indonesia (Idealog), 2021)
Nowadays, apart from being used for a place to rest and socialize, a house is often used as an economic activity, such as trade, services or production. As can be found in the settlements of Kampung Mahmud, Margaasih sub-district, Bandung Regency, there are home-scale furniture businesses that have been passed down between generations, so it can be found about the use of space in the area behind the house for the place of business. This study will describe the use of the back room of the house as a home industry scale furniture production business space with the emphasis of the study on: 1) space layout and circulation of the workflow in it, and 2) types, functions, and ergonomics of production tools. reviewed from anthropometry. The method used is descriptive and analytical, through field observations, interviews, and reference studies. The purpose of this research is identified changes in function, either through the addition or modification of the use of space related to economic activities. The results showed that the furniture production room has a sufficient area, with adequate production facilities and equipment. By having 1 (one) access, the production room requires a proper arrangement of equipment layout, so that the circulation of workers is not disturbed and the production process is more efficient. Based on the ergonomic evaluation, it was found that there were machines that did not meet the anthropometric requirements, namely the smoothing machine and the grinding machine, both of which could be added to the height to avoid a bending position when operating them. Keywords : Production Room, Furniture, Layout, Workflow, Ergonomics, Anthropometry